The Influence of Corporate Social Responsibility Disclosure and Capital Structure on Earning Response Coefficient of Indonesian Mining Companies - Arja Sadjiarto; Nikolaus Evan (Accounting Department, School of Business and Management - Universitas Kristen Petra, 2023)
This study aims to examine the influence of CSR disclosure and capital structure on ERC (Earning Response Coefficient) in mining companies listed on the Indonesia Stock Exchange (BEI) in the year 2018 – 2021. The result of the study will add findings regarding this topic for Indonesian mining companies which includes the period of pandemics. This research utilizes multiple linear regression using SPSS version 29 program. The findings of this study indicate that CSR disclosure has a significant negative influence on ERC. Meanwhile, capital structure does not have an impact on ERC.